2014
DOI: 10.1021/jp506203k
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrophilicity and Length of Diblock Arms for Determining Star Polymer Physical Properties

Abstract: We present a molecular simulation study of star polymers consisting of 16 diblock copolymer arms bound to a small adamantane core by varying both arm length and the outer hydrophilic block when attached to the same hydrophobic block of poly-δ-valerolactone. Here we consider two biocompatible star polymers in which the hydrophilic block is composed of polyethylene glycol (PEG) or polymethyloxazoline (POXA) in addition to a polycarbonate-based polymer with a pendant hydrophilic group (PC1). We find that the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…It is interesting to note that the DVB-PS-PEGMA star is well-fit by the Dozier model of a swelled star polymer -a model which is better able to resolve the smaller scale structure in the higher Q regions manifested as "blob" scattering from individual arm chains that are more solvent exposed. This property of DVB-PS-PEGMA is well appreciated, and we have shown previously [30] using molecular dynamics on a related PEG star polymer, that the thermodynamic origins of a structural transition as temperature increases is consistent with entropy-driven dehydration such that below the lower critical solution temperature the PEG arms act like a Gaussian random coil. Thus the DVB-PS-PEGMA star polymer serves as a reference point for introduction of monomer units that are in fact sensitive to pH.…”
Section: Resultssupporting
confidence: 58%
“…It is interesting to note that the DVB-PS-PEGMA star is well-fit by the Dozier model of a swelled star polymer -a model which is better able to resolve the smaller scale structure in the higher Q regions manifested as "blob" scattering from individual arm chains that are more solvent exposed. This property of DVB-PS-PEGMA is well appreciated, and we have shown previously [30] using molecular dynamics on a related PEG star polymer, that the thermodynamic origins of a structural transition as temperature increases is consistent with entropy-driven dehydration such that below the lower critical solution temperature the PEG arms act like a Gaussian random coil. Thus the DVB-PS-PEGMA star polymer serves as a reference point for introduction of monomer units that are in fact sensitive to pH.…”
Section: Resultssupporting
confidence: 58%
“…These include the details of the formulation process, by which a hydrophobic drug is loaded into a polymeric nanoparticle. Earlier work has shown that when the nanoparticles are placed in water, the hydrophobic effect serves as a driving force to cause the hydrophobic core and any hydrophobic arm-blocks to reorganize into an approximately spherical and compact region while the hydrophilic arm-blocks remain solvated. Consequently, in water, not only is it difficult to dissolve hydrophobic drug molecules, but the polymeric nanoparticle may not be able to adopt conformations conducive to drug-loading.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the dearth of atomic-level information that is currently available from experiments involving nanogel star polymers and the pressing need to move toward the rational exploration of the space of polymeric materials, molecular dynamics simulations have been used in a predictive capacity to provide much-needed information about these systems. All-atom simulations of star polymers have proven their utility in providing an atomic-level picture of the structural and kinetic behavior of these systems, elucidating the dependence of these behaviors on factors such as temperature and the chemical composition of the core and arms. Additionally, coarse-grained simulations have provided insight into factors controlling the synthesis of these nanoparticles, outlining the influence of parameters, such as composition, concentration, and reactant ratios, on the size distributions and atomic-level architecture of the resulting product nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…These results verify recent MD simulations that show segmental packing of VL blocks upon a small cross-linked CL core. 25,32,33 MD simulations further suggest tBuCL segments pack less effectively than VL. 32 This poorer packing may enhance the mobility within the hydrophobic core to reduce shape anisotropy under the interfacial tension with water.…”
Section: ■ Results and Discussionmentioning
confidence: 96%